The utilization of new media technology in improving the effectivess of teaching and learning in UNIMAP: A study - Ismail, Adila; Azahari, Nur Azila; Abdul Rahim, Edzham Armin; Affandy, Habee Bullah (2016)
This paper illustrates the findings of the study on utilization of new media technology in improving the effectiveness of teaching and learning in Universiti Malaysia Perlis (UniMAP), Malaysia.This study has been conducted in UniMAP, with 500 students from various study backgrounds as respondents.This study uses a quantitative method, with a set of questionnaire is used in data collection.With that, the end result of the research will include the use of the technology in the students’ dayto-day activities. Lastly, a conclusion is made on how the use of new media technology is effective and beneficial to daily teaching and learning activities.